2017
DOI: 10.1159/000478068
|View full text |Cite
|
Sign up to set email alerts
|

Liver Kinase B1/AMP-Activated Protein Kinase Pathway Activation Attenuated the Progression of Endotoxemia in the Diabetic Mice

Abstract: Background/Aims: Sepsis is a common disease that continues to increase in prevalence worldwide, and diabetes mellitus may make the situation worse. This study was designed to determine the role of Liver Kinase B1 (LKB1)/adenosine monophosphate-activated protein kinase (AMPK) signaling pathway in diabetic mice complicated with systemic endotoxemia. Methods: The effects of LKB1/AMPK signaling pathway activation on endotoxemia were investigated in streptozotocin induced diabetic mice (STZ-mice) and db/db diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…In previous studies, AMPK has been identified as an enzyme that regulates Sirt3 by promoting the expression of peroxisome-activator receptor coactivator-1α (PGC-1α) as well as oxidative stress in autophagy (Palacios et al, 2009;Giralt et al, 2011;Kahn et al, 2015;Pillai et al, 2015). This is in line with the study of Yang et al (2017) which also reported a notable decrease in liver kinase B (LKB1), followed by decreased phosphorylation of AMPK and its downstream kinase, namely acetyl coenzyme A carboxylase (Acc) at serine residue 79.…”
Section: Sirt3/ampk Pathwaysupporting
confidence: 67%
“…In previous studies, AMPK has been identified as an enzyme that regulates Sirt3 by promoting the expression of peroxisome-activator receptor coactivator-1α (PGC-1α) as well as oxidative stress in autophagy (Palacios et al, 2009;Giralt et al, 2011;Kahn et al, 2015;Pillai et al, 2015). This is in line with the study of Yang et al (2017) which also reported a notable decrease in liver kinase B (LKB1), followed by decreased phosphorylation of AMPK and its downstream kinase, namely acetyl coenzyme A carboxylase (Acc) at serine residue 79.…”
Section: Sirt3/ampk Pathwaysupporting
confidence: 67%
“…Metformin (5mM for in vitro studies, and 400mg/kg bid for in vivo studies) decreases permeability in endothelial cells stimulated with high glucose and LPS as well as improving lung barrier integrity in both STZ-induced diabetic and db/db mice models; the mechanism is linked to the activation of the LKB1/AMPK pathway (Y. Yang, et al, 2017).…”
Section: Improved Vascular Integritymentioning
confidence: 99%
“…It is demonstrated that during sepsis, the inflammation leads to cellular signaling alteration, increase in LPO and ROS concentrations, neutrophil hyperactivity, and infiltration of MPO into different tissues and organs [22][23][24][25][26][27]. Several studies have reported that administration of metformin during sepsis can improve mitochondrial function, accelerate bacterial clearance, strengthen intracellular junctions, and alleviate edema and organ necrosis [28][29][30][31][32][33][34][35][36][37][38]. Besides, metformin administration can reduce the oxidative stress level in the blood, brain, and pancreas 9-72 hrs.…”
Section: Discussionmentioning
confidence: 99%